1992
DOI: 10.1111/j.1471-4159.1992.tb08911.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Depletion Preferentially Impairs D1 over D2‐Receptor Regulation of Striatal In Vivo Acetylcholine Release

Abstract: The roles of D2 and D1 dopaminergic receptors on the regulation of striatal acetylcholine (ACh) release in vivo were examined for a period of 120 min after acute (2 h) or prolonged (16 h) depletion of brain dopamine (DA) by alpha-methyl-p-tyrosine. The reduction of DA transmission did not affect basal ACh output after 2 h but markedly lowered ACh release by 16 h (50%). Acute alpha-methyl-p-tyrosine pretreatment prevented the reduction of ACh release by the D1 antagonist SCH 23390 and its increase by the D2 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 12 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…A major component of the dopaminergic regulation of cholinergic function is mediated by D 2 receptor inhibition of spike-driven Ca 2ϩ influx and acetylcholine release (Lehmann and Langer, 1983;Bertorelli et al, 1992;Stoof et al, 1992;DeBoer et al, 1993;Di Chiara et al, 1994;. However, there are compelling reasons to believe there is more to this story.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A major component of the dopaminergic regulation of cholinergic function is mediated by D 2 receptor inhibition of spike-driven Ca 2ϩ influx and acetylcholine release (Lehmann and Langer, 1983;Bertorelli et al, 1992;Stoof et al, 1992;DeBoer et al, 1993;Di Chiara et al, 1994;. However, there are compelling reasons to believe there is more to this story.…”
Section: Discussionmentioning
confidence: 92%
“…This modulation could account, in part, for conjectured involvement of D 1 -class receptors in generation of the pause (Watanabe and Kimura, 1998). These alterations in intrinsic properties governing autonomous spiking complement the direct D 2 receptormediated inhibition of acetylcholine release (Lehmann and Langer, 1983;Bertorelli et al, 1992;Stoof et al, 1992;DeBoer et al, 1993;Di Chiara et al, 1994;, further reducing the impact of cholinergic interneurons on striatal circuitry.…”
Section: Is the Reduction Of Namentioning
confidence: 99%
See 1 more Smart Citation
“…DD mice exhibited a decrease in ChAT expression, with a reduction of extracellular ACh levels in the striatum, demonstrating that the cholinergic system was suppressed in DD mice. DA depletion that is induced by α -methyl- p -tyrosine and reserpine was shown to decrease basal ACh release in the striatum ( Bertorelli et al , 1992 ). In addition, ChAT activity has been reported to be normal or reduced in the striatum in PD patients ( Hornykiewicz and Kish, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic contacts from intrinsic striatal neurons mainly arise from substance P-containing MSp GABAergic neurons (Bolam et al, 1986;Bolam and Izzo, 1988;Martone et al, 1992), although some input may come from enkephalin-containing striatal MSp neurons (Martone et al, 1992). Furthermore, it has been suggested that the effect of systemically administered indirect DA agonists, such as amphetamine, on the striatal ACh output is mediated in part by GABAergk MSp neurons (Consolo et al, 1991Bertorelli et al, 1992) or corticostriatal or thalamostriatal glutamatergic projections (Damsma et al, 1991;DeBoer et al, 1993), which have a direct effect on striatal cholinergic neurons and GABAergic MSp neurons.…”
mentioning
confidence: 99%